Late gadolinium enhancement of the hinge point is a common finding in asymptomatic ELITE athletes. (11th May 2022) - Verwijs, SM; Van Hattum, JC; Spies, JL; Boekholdt, SM; Planken, RN; Groenink, M; Van Randen, A; Van Luijk, RD; Van Den Berg-Faaij, AM; Bakermans, AJ; Nederveen, AJ; Moen, MH; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Late gadolinium enhancement (LGE) demonstrates regional differences in myocardial extracellular volume, such as seen in myocardial fibrosis, and is associated with diverse cardiac diseases and is a predictive factor for sudden cardiac death. Earlier findings suggest an LGE prevalence of 7% in endurance athletes of varying age and exercise exposure. However, findings for (potentially benign) LGE indices in athletes performing at elite-level are lacking. Purpose: To establish a specific baseline for LGE findings on CMR in apparently healthy, elite-level athletes. Methods: We performed a cross-sectional assessment of hinge point late gadolinium enhancement (HP-LGE) in elite athletes (national-, international-, Olympic-, Paralympic-level or comparable). All athletes were asymptomatic and examined during pre-participation cardiovascular screening. Each underwent CMR using 3 Tesla- (Philips) or 1½ Tesla- (Siemens) MRI-scanners including short-axis cine imaging, LGE, and T1-mapping. CMR data were analysed using cvi42, statistical analyses using R. Athletes with HP-LGE were compared to athletes without HP-LGE. Results: We screened 210 athletes, 34% female, with a mean age (±SD) of 28±7 and body surface area (BSA) of 2.0±0.2 m2 participating in road cycling (n=38), field hockey (n=28), water polo (n=27), soccer (n=21), rowing (n=18), swimming (n=13), track cycling (n=12), tennis (n=10), sailing (n=10), para-cycling (n=7), and miscellaneous (n=26) sports. We observed indexed end-diastolic volumes (EDVi) of 119±20 and 123±20 ml/m2, stroke volumes 131±33 and 127±37 ml, and ejection fractions of 56±5 and 54±6 %, in the left- (LV) and right ventricle (RV), respectively. Eighty-four (40%) athletes had HP-LGE. Proportionally, fewer female athletes had HP-LGE as compared with men (24 vs 41 %, p=0.014). Athletes with HP-LGE had greater LV- and RV EDVi (123±20 and 127±20 ml/m2 vs. 117±19 and 120±19 ml/m2, p=0.02 and p=0.01; for LV and RV, respectively), lower RV ejection fractions (53±5 vs. 55±6, p-value 0.04), smaller estimated global extra cellular volumes of the LV (24 vs 25 %, p=0.01). There were no differences in indexed LV- and RV end-systolic volumes, LV- and RV stroke volumes, LV ejection fraction and indexed wall mass, global native-, or contrast-enhanced T1 times in athletes with and without HP-LGE. Conclusion: Late gadolinium enhancement in the hinge point is present in 40% of asymptomatic elite athletes. Athletes with HP-LGE were more frequently men, had higher LV- and RV EDVi, suggesting an association with ventricular volumes. Our findings in asymptomatic, elite athletes, with normal ventricular function and T1 times, suggest that HP-LGE could be a sign of physiological sports adaptation instead of an early sign of pathology. Further studies are warranted to investigate if HP-LGE is associated with long-term cardiac changes or the development of cardiac pathology.